HUBUNGAN PROTEIN KASAR TERCERNA DAN SERAT KASAR TERCERNA TERHADAP PRODUKSI GAS METAN PADA DOMBA LOKAL JANTAN: THE CORRELATION OF CRUDE PROTEIN DIGESTIBLE AND CRUDE FIBER DIGESTIBLE ON METHANE GAS PRODUCTION IN INDIGENOUS RAMS - Saputro, Wahyu Subagio; Efendi, Kabib; Darmawan, Muhammad Arif (Universitas Boyolali, 2024)
This research aims to examine the correlation between digestible crude protein (DCP) and digestible crude fiber (DCF) on methane gas production from fermented rice straw using urea and urine. The material in this study was used included eight indigenous rams aged ± 1.5 years with a weight of ± 20 kg. The feed provided consisted of concentrate and rice straw fermented with urea (P1) and rice straw fermented with urine (P2). Feed was given twice daily, and water was provided ad libitum. Data collection of digestible crude protein and digestible crude fiber was conducted by total collection method in metabolic cages for 7 days, while methane gas production measurement was conducted for 2 x 24 hours. The results showed differences in correlation values between the two types of treatments. Treatment with rice straw fermented with urea had correlation values of 0.937 for digestible crude protein and 0.507 for digestible crude fiber with coefficient of determination values of 87.9% for DCP and 25.7% for DCF. Meanwhile, in the treatment with rice straw fermented with urine, the correlation values were -0.632 for DCP and -0.991 for DCF with coefficient of determination values of 40.0% for DCP and 98.3% for DCF. The conclusion from this research is that the difference in correlation values is caused by the nitrogen source used for fermentation and the presence of accompanying compounds found in cattle urine used for rice straw fermentation.